Correction: Navigating the winds of change: strategic foresight and the power of weak signals - Jason Jabbour; Debra J Davidson; Henrik Carlsen; Nicholas King; Simone Lucatello; Salvatore Aricò; Fang Lee Cooke; Ranjan Datta; Peter Gluckman; Edgar E. Gutierrez-Espeleta; Andrea Hinwood; Gensuo Jia; et al. (Sustainability Science, 2026)

Navigating the winds of change: strategic foresight and the power of weak signals - Jason Jabbour; Debra J Davidson; Henrik Carlsen; Nicholas King; Simone Lucatello; Salvatore Aricò; Fang Lee Cooke; Ranjan Datta; Peter Gluckman; Edgar E. Gutierrez-Espeleta; Andrea Hinwood; Gensuo Jia; et al. (Sustainability Science, 2026)
In an era of increased complexity, interdependence, uncertainty and rapidly advancing technology, the ability to identify and swiftly adapt to current and future trends is key to progressing sustainability. Intersecting drivers and stressors are converging to destabilize socioecological systems and reshape national, regional and global outlooks. The intersecting and converging crises of the 21st century have exposed the limits of planning that relies too heavily on linear extrapolations from well-known global/mega-trends. This study explores whether a limited number of emerging trends that only manifest as weak signals today serve as central conduits (super-nodes) for amplifying and accelerating systemic disruption. Using an exploratory mixed-methods design, a global Delphi survey ( N = 790, 132 countries) generated 1200 horizon-scan items, inductively coded into 29 clusters. Scenario stress-testing distilled the findings into 280 candidate weak signals—ranked by likelihood, impact, and timing—from which 20 were shortlisted and mapped onto a 20 × 20 influence matrix through structured expert debate. Weighted degree centralities and a 10,000-run bootstrap test identified statistically significant hubs. Results suggest that anticipatory governance can be strengthened by prioritizing high-centrality signals and institutionalizing ongoing weak-signal scanning alongside transparent, multi-source decision-making to avoid cascading risks across planetary-health, economic, and technological systems. At the midpoint of a decade dominated by disruption–climate change, pandemic, geopolitical upheaval, widening inequality, war, misinformation and the rapid rise of Artificial Intelligence–we posit that strategic foresight and informed anticipation is a critical imperative in the pursuit of a global common good and a resilient future.

Key groundwater indicators for sustainable social-ecological systems in drylands: a Mexican perspective - Víctor Manuel Reyes-Gómez; Elisabeth Huber-Sannwald; Luis Carlos Bravo-Peña; Gerardo Esquivel-Arriaga; Natalia Martínez-Tagueña; Simone Lucatello; Juana Claudia Leyva-Aguilera; Georges Seingier; David Borre (Groundwater for Sustainable Development, 2025)

Can we pull resilience from the rubble? experiencing earthquakes in Mexico City - Irasema Alcántara-Ayala; Simone Lucatello; Daniel Rodríguez-Velázquez (Natural Hazards, 2024)
This paper serves as an introduction to focus on the meaning of resilience as a notion that hypothetically enables cities and their citizens to remain unaffected by shocks and stresses of diverse nature, but in practice, is a parsimonious representation of a highly complex human endogenous condition that is often not adequately understood and addressed due to weak or weathered disaster risk governance. Through an empirical analysis, the relevance of the occurrence of disasters such as the one produced by the Mexico City earthquake of September 19, 2017, and its relationship to the meaning of urban resilience is addressed. Since the 100 Resilient Cities program launch in 2013, several cities, including Mexico City, have adopted diverse strategies to build and become more resilient to physical, social, and economic shocks and stresses. Nonetheless, the degree of success of such strategies expressed in everyday life within the cities, regardless of what the official documents report, reveals highly heterogeneous results. In the case of Mexico City, it is evident that the appropriate strategy for attaining the desired outcome of becoming a Resilient City has not been successful. Despite setting the goal of advancing disaster risk reduction through urban and regional planning, the impact of the earthquake of September 19, 2017, proved otherwise.

Under the rubble: disaster risk management and accountability after the Mexico City earthquake of September 19, 2017 - Irasema Alcántara-Ayala; Daniel Rodríguez-Velázquez; Simone Lucatello (Natural Hazards, 2024)